Efeitos da radiação gama na qualidade de morangos cv. Albion - Anna Lidya da Cunha Quintão (2018)
Strawberry is a very perishable fruit with a maximum shelf life of 3 days at room temperature being vulnerable to post-harvest deterioration, even when stored under refrigeration.Gamma radiation technology has the ability to inactivate microorganisms without changing the temperature, avoiding the deterioration of the taste, color and nutritional value of foods such as those caused by heat. In this context, the present work aimed to determine the period of conservation with quality in strawberries submitted to different doses of gamma irradiation. The strawberries were submitted to doses of gamma irradiation 0; 0.8; 1.6 and 2.4 kGy and stored for up to 9 days at 10±1 °C and 90±5% RH. The analyzes were performed every 3 days from day 0, and the anthocyanins were analyzed by the differential pH method, the phenolic compounds by the colorimetric method and the profile of these compounds by the chromatographic method. The ascorbic acid was determined by the chromatographic method and the colorimetric properties were performed using a colorimeter with determination in the system CIE L* a* b*. In the microbiological analyzes, the most probable numbers of total coliforms and thermotolerant coliforms, mold and yeast counts and Salmonella spp. Irradiation in low doses and under refrigeration allowed an increase of three days in the commercialization period of the strawberries.The irradiation treatment did not interfere with the anthocyanin content over the assessed storage time. It was possible to observe that the doses used did not influence the loss of the phenolic compounds, occurring the maintenance of these compounds with the application of the gamma radiation throughout the storage. It was verified that the variation in ascorbic acid values may be due to the post-harvest storage of the fruits and not to the irradiation treatment. The applied doses did not interfere in the characteristic red color of the strawberry. For the correlation of the data, few moderate positive correlations were found among the quantitative variables. The fruits irradiated at dose 2.4 kGy were more efficient in the control of microorganisms during the evaluated period, being the best dose to be used to increase the shelf life of the strawberries of the cv. Albion.